2018
DOI: 10.1001/jamaophthalmol.2017.6090
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Binocular Video Game vs Placebo Video Game for Improving Visual Functions in Older Children, Teenagers, and Adults With Amblyopia

Abstract: IMPORTANCE Binocular amblyopia treatment using contrast-rebalanced stimuli showed promise in laboratory studies and requires clinical trial investigation in a home-based setting.OBJECTIVE To compare the effectiveness of a binocular video game with a placebo video game for improving visual functions in older children and adults. DESIGN, SETTING, AND PARTICIPANTSThe Binocular Treatment of Amblyopia Using Videogames clinical trial was a multicenter, double-masked, randomized clinical trial. Between March 2014 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
137
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 122 publications
(143 citation statements)
references
References 37 publications
2
137
2
2
Order By: Relevance
“…The composite BF score has been successfully used in recent amblyopia treatment trials for analysis of treatment effects . The scale is ordinal, rather than continuous, therefore, outcomes are analysed with non‐parametric statistics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The composite BF score has been successfully used in recent amblyopia treatment trials for analysis of treatment effects . The scale is ordinal, rather than continuous, therefore, outcomes are analysed with non‐parametric statistics.…”
Section: Discussionmentioning
confidence: 99%
“…The composite BF score has been successfully used in recent amblyopia treatment trials for analysis of treatment effects. 8,9 The scale is ordinal, rather than continuous, therefore, outcomes are analysed with non-parametric statistics. We have shown that the composite score highly correlates with both a measure of inter-ocular suppression and with a threshold measure of stereoacuity that tests coarse levels of binocular disparity detection beyond the range of common clinical tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BRAVO study was a placebo-controlled, doublemasked randomised clinical trial of an iPod-based binocular videogame treatment for amblyopia in older children and adults (see Guo, Babu & Black et al 33 for the full study protocol and Gao, Guo, Babu et al 34 for the trial results). The trial included participants with unilateral amblyopia due to anisometropia and/or strabismus who were not currently undergoing any amblyopia therapy apart from wearing refractive correction.…”
Section: Participantsmentioning
confidence: 99%
“…A growing body of literature demonstrates that vision can improve in adult humans with amblyopia through interventions such as monocular [21,22] and binocular [23][24][25][26][27] perceptual learning and non-invasive brain stimulation [28][29][30][31][32]. However, these approaches have not yet translated into positive randomized clinical trials in adult patients that are required for translation into clinical practice [33].…”
Section: Introductionmentioning
confidence: 99%